SiMaYang Type II Learning Model Assisted by Kahoot Application: Its Impact in Improving Student's Concept Understanding Based on Apos Theory - Nabila Ariyana; Fredi Ganda Putra (Online Learning In Educational Research (OLER), 2021)
This research aims to determine the effect of the SiMaYang type II learning model assisted by the Kahoot application in increasing students' concept understand based on the APOS theory. This research is quasi-experimental with posttest only control group design. The sample of this research consisted of 67 students who were divided into three classes. The sampling technique used was the class random sampling technique. The research instrument was declared valid with a good difficulty level and reliable. Therefore, it could be used to collect data on students' conceptual understanding. Furthermore, the One-Way ANOVA test was used to test the hypothesis with a significant level of five percent. This research shows that the SiMaYang type II learning model assisted by the Kahoot application positively influenced students' conceptual understanding.